The Impact of Atmospheric and Tectonic Constraints on Radon-222 and Carbon Dioxide Flow in Geological Porous Media - A Dozen-Year Research Summary - Zafrir, Hovav; Barbosa, Susana; Levintal, Elad; Weisbrod, Noam; Ben Horin, Yochai; Zalevsky, Zeev (Frontiers in Earth Science, 2020)
Long-term monitoring of Rn-222 and CO2 at a depth of several tens of meters at the Sde-Eliezer site, located within one of the Dead Sea Fault Zone (DSFZ) segments in northern Israel, has led to the discovery of the clear phenomenon that both gases are affected by underground tectonic activity along the DSFZ. It may relate to pre-seismic processes associated with the accumulation and relaxation of lithospheric stress and strain producing earthquakes. This approach assumes that the climatic influence on Physico-chemical parameters is limited at depth since its strength decreases with the increase in the thickness of the geological cover. Hence, the monitoring of natural gases in deep boreholes above the water table enables to reduce the climatic-induced periodic contributions, and uncover the residual portion of the signals that seem to be associated, as indicated recently with regional geodynamic processes. The plausible pre-seismic local movement of the two gases at depth, is identified by the appearance of discrete, random, non-cyclical signals, wider in time duration than 20 hours and clearly wider than the sum of the width of the periodic diurnal and semidiurnal signals driven by ambient climatic parameters. These non-cyclical signals may precede, by one day or more, a forthcoming seismic event. Hence, it is plausible to conclude that monitoring of any other natural gas that is present at depth, may show a similar broadening signal and may serve as a precursor too. The necessary technical conditions enabling to distinguish between anomalous signals of gases that may be induced locally by pre-seismic processes at depth, and the relatively low periodic signals that are still established at depth related to external climatic conditions, are presented in detail.